Cross-Cultural Adaptation and Validation of the Chinese Version of the Brace Questionnaire - Honglei Yi; Hu Chen; Xinhui Wang; Hong Xia; Hong Xia (Frontiers Media S.A., 2022)
Objective: To adapt the questionnaire cross-culturally and to analyze the adaptation and validation of the Chinese version of the Brace Questionnaire (C-BrQ).Methods: The adaptation was based on the International Quality of Life Assessment Project guidelines. A total of 79 patients with AIS were included to examine the psychometric properties of the C-BrQ. The reliability was assessed using internal consistency (the Cronbach's alpha coefficient) and test-retest reliability (intraclass correlation coefficient ICC2.1, 95% CI). Floor and ceiling effects were calculated. Lin's concordance correlation coefficient (CCC, 95% CI) was used to compare the agreement between the Scoliosis Research Society-22 patient questionnaire (SRS-22) and C-BrQ.Results: There were strong correlations between each item and its corresponding domain significantly. The correlations between the C-BrQ domains and their related questions vary from moderate to strong (r = 0.311-0.933, P < 0.05). The Cronbach's was 0.891, showing good internal consistency of each domain of the BrQ, and the ICC in test-retest was 0.860 (0.8776, 0.912), which means an excellent test-retest reliability. The Lin's CCC between SRS-22 and C-BrQ was 0.773 (0.669, 0.848), showing great agreement. However, no significant floor and ceiling effects in C-BrQ was observed except the ceiling effect in school activity and bodily pain.Conclusion: BrQ was translated and cross-culturally adapted for use in China with good internal consistency and excellent test-retest reliability.